Mapping Fuzzy Petri Net to Fuzzy Extended Markup Language - Zahra Masoudinezad; Ali Haroon Abadi; Mohammad Teshnehlab (International Journal of Electrical and Computer Engineering (IJECE), 2013)
Use of model gives the knowledge and information about the phenomenon also eradicates the cost, the effort and the hazard of using the real phenomenon. Characteristics and concepts of Petri nets are in a way that makes it simple and strong to describe and study the information processing system; especially it is shown in those which are dealing with discrete, concurrent, distributed, parallel and indecisive events. Yet, due to Petri nets inability to face with systems working on obscure data and continues events, the interest to develop fundamental concept of Petri nets has been raised which is led to new style of presented model named "fuzzy Petri nets". The difference in Petri nets is in the elements that have been fuzzed. Transitions, places, signs and arcs can be fuzzed. PMNL, on the other hand as a markup language has been engaged in uttering Petri nets in previous researches. Fuzzy markup nets can model the uncertainty of concurrent scenarios different from a dynamic system by a board of parameters and use of fuzzy membership dependencies. Therefore, in order to define these uncertain data, it is vital to use a formal language to describe fuzzy Petri nets. To support this version in this thesis, a markup language will be presented stating the structure and grammar of markup language and covering fuzzy concepts in Petri nets as well. Presenting the suggested grammar accommodates the support of fuzzy develope.DOI:http://dx.doi.org/10.11591/ijece.v3i5.4035